Button up! : wrinkled rhymes - Schertle, Alice (Harcourt Children's Books/ Houghton Mifflin Harcourt, 2009)
From undies to jammies to a much-loved hand-me-down sweatshirt, the talking clothes in these poems know just who they are and who's wearing them.